Quantum Coherence Times Enhancement in Vanadium(IV)-based Potential Molecular Qubits: the Key Role of the Vanadyl Moiety - Atzori, Matteo; Morra, Elena; Tesi, Lorenzo; Albino, Andrea; Chiesa, Mario; Sorace, Lorenzo; Sessoli, Roberta (Journal of the American Chemical Society, 2016)
In the search for long-lived quantum coherence in spin systems, vanadium(IV) complexes have shown record phase memory times among molecular systems. When nuclear spin-free ligands are employed, vanadium(IV) complexes can show at low temperature sufficiently long quantum coherence times, T m, to perform quantum operations, but their use in real devices operating at room temperature is still hampered by the rapid decrease of T 1 caused by the efficient spin–phonon coupling. In this work we have investigated the effect of different coordination environments on the magnetization dynamics and the quantum coherence of two vanadium(IV)-based potential molecular spin qubits in the solid state by introducing a unique structural difference, i.e., an oxovanadium(IV) in a square pyramidal versus a vanadium(IV) in an octahedral environment featuring the same coordinating ligand, namely, the 1,3-dithiole-2-thione-4,5-dithiolate. This investigation, performed by a combined approach of alternate current (ac) susceptibility measurements and continuous wave (CW) and pulsed electron paramagnetic resonance (EPR) spectroscopies revealed that the effectiveness of the vanadyl moiety in enhancing quantum coherence up to room temperature is related to a less effective mechanism of spin–lattice relaxation that can be quantitatively evaluated by the exponent n (ca. 3) of the temperature dependence of the relaxation rate. A more rapid collapse is observed for the non-oxo counterpart (n = 4) hampering the observation of quantum coherence at room temperature. Record coherence time at room temperature (1.04 μs) and Rabi oscillations are also observed for the vanadyl derivative in a very high concentrated material (5 ± 1%) as a result of the additional benefit provided by the use of a nuclear spin-free ligand.